Roadmapping in Developing Countries - Anthony Clayton (Foresight and STI Governance)
The paper complete a series of two publications of the author (for the first paper «Technology Roadmaps: Tools for Development» see №3/2008). It contains an in-depth analysis of political, economic and social factors affecting the economic progress of developing countries. The case study of Jamaica demonstrates an attempt to overcome the path-dependency effect, caused by the conventional government’s focus on the development of sugar industry. The Foresight exercise is revealed a number of possible scenarios allowing for much more attractive economic and social conditions and contributed to the revision of the Jamaica’s technological priorities.